Disseminated tumor cells from the bone marrow of patients with nonmetastatic primary breast cancer are predictive of locoregional relapse - Hartkopf, Andreas; Wallwiener, Markus; Fehm, T. N.; Hahn, M.; Walter, C. B.; Gruber, I.; Brucker, S. Y.; Taran, F. -A. (Annals of oncology, 2015)
Background - Disseminated tumor cells (DTCs) are detectable in the bone marrow (BM) of patients with primary breast cancer (PBC) and predictive of an impaired prognosis. This large trial aimed to analyze the impact of DTC detection on locoregional relapse (LR). - Patients and methods - Patients with nonmetastatic PBC were eligible for this analysis. BM aspiration (BMA1) was carried out during primary surgery and DTCs were detected by using immunocytochemistry (A45-B/B3 antibody against pancytokeratin) and morphological criteria. At the time of LR, a subgroup of patients with nonmetastatic and operable LR received a secondary BM aspiration (BMA2). - Results - A total of 3072 patients were included into the analysis. Of these, 732 (24%) presented with DTCs at BMA1. One hundred thirty-nine patients experienced LR and 48 of these (35%) were initially DTC positive. DTC detection was significantly associated with an increased risk of LR in univariate (P = 0.002) and multivariate analysis (P = 0.009) with a hazard ratio of 1.65 (95% confidence interval 1.13-2.40). Of the patients with LR, 55 patients were available for BMA2 and 17 of these (32%) were DTC positive. DTC detection at the time of LR was indicative of impaired overall survival (univariate analysis, P = 0.037). - Conclusions - DTC detection in patients with PBC is associated with an increased risk of LR, indicating that tumor cells may have the ability to recirculate from the BM to the site of the primary tumor. The impaired prognosis associated with DTC detection at the time of LR may help to identify patients that are in need for additional or more aggressive treatment.